1988
DOI: 10.1002/chin.198843022
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Electrocatalysis by Ad‐Atoms. Part 23. Design of Platinum Ad‐Electrodes for Formic Acid Fuel Cells with Ad‐Atoms of the IVth and the Vth Groups.

Abstract: 022ChemInform Abstract The ad-atoms of the IVth and Vth periodic groups cause a very strong enhancement of the activity of Pt. The optimum coverages with these ad-atoms are determined from steady-state current-potential curves on smooth ad-electrodes to be 0.5. The ad-atoms Pb, Bi, and Sb enhance the activity by about three orders of magnitude. The higher the activity of the ad-electrode, the higher is the tolerance against poisoning. A method of preparation of ad-electrodes with high-specific surface area is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Other Pt-based alloys have been tested in formic acid/formate electrooxidation such as PtFe [ 79 ], PtAu [ 67 , 90 ], PtAg [ 65 ], PtCo [ 66 ], PtCu [ 68 ], PdPt [ 39 , 71 , 73 , 91 , 92 ], PtBi [ 69 , 93 ] or PtSn [ 68 , 93 , 94 ] ( Table 2 ). Indeed, the use of Bi, Sb, As, Pb, Sn and Ge as dopants for Pt has been investigated from several decades ago, finding optimum loadings of around 50% in most cases [ 93 , 94 ]. Adzic et al even added these dopants in situ, by electrodeposition on Pt electrodes, leading to enhanced electrooxidation of formic acid.…”
Section: Platinum For Formic Acid/formate Electrooxidationmentioning
confidence: 99%
“…Other Pt-based alloys have been tested in formic acid/formate electrooxidation such as PtFe [ 79 ], PtAu [ 67 , 90 ], PtAg [ 65 ], PtCo [ 66 ], PtCu [ 68 ], PdPt [ 39 , 71 , 73 , 91 , 92 ], PtBi [ 69 , 93 ] or PtSn [ 68 , 93 , 94 ] ( Table 2 ). Indeed, the use of Bi, Sb, As, Pb, Sn and Ge as dopants for Pt has been investigated from several decades ago, finding optimum loadings of around 50% in most cases [ 93 , 94 ]. Adzic et al even added these dopants in situ, by electrodeposition on Pt electrodes, leading to enhanced electrooxidation of formic acid.…”
Section: Platinum For Formic Acid/formate Electrooxidationmentioning
confidence: 99%
“…Different from Sb UPD on Pt surfaces [20,25], coverage of Sb (θSb, a coefficient based on the ratio of Pd sites filled and not filled) on Pd surface was tuned by controlling the UPD time. In this paper, Sb UPD on fresh Pd films was performed for 10 s, 20 s, 30 s, respectively.…”
Section: Sb Upd On Pd Film Electrodesmentioning
confidence: 99%
“…The electronic effect leads to a weakening of the CO-Pd interaction [27] and makes the direct pathway of formic acid oxidation being predominant [23]. In bi-functional mechanism, Sb adatoms provide active sites for -OH formation at lower potentials than on pure Pd, and -OH promotes the oxidative removal of adsorbed poisoning intermediates during formic acid oxidation [18,20,28].…”
Section: Sb Mupd On Pd Film Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally, it was observed that the adsorption of some foreign adatoms enhanced the electrochemical reaction rate. The most relevant papers, in which fundamental interpretation of data is attempted, can be found in the works by S. Motoo, who classified the effect of surface adatoms on polycrystalline platinum into three groups: i) those inducing electronic effects to the surface of the material, ii) those acting as a third body, simply inhibiting the dehydration reaction and iii) those playing a bifunctional role, in such a way that they would easily adsorb oxygen suitable to oxidize adsorbed CO at lower potentials than on pure platinum [6,7].…”
Section: A N U S C R I P T Introductionmentioning
confidence: 99%